PANGAN FERMENTASI SEBAGAI PANGAN FUNGSIONAL: PERSPEKTIF NUTRISI DAN KESEHATAN - Eka Wijayanti; Widia Pangestika; Rifatul Masrikhiyah (Journal of Technology and Food Processing (JTFP), 2026)
Fermented foods are a type of functional food that has been extensively studied due to their potential to enhance nutritional value and provide health benefits. This journal review aims to analyse the role of fermented foods as functional foods from a nutritional and health perspective. The method used was a narrative literature review, examining ten scientific articles on various fermented foods, including fermented wheat, probiotic yoghurt, fermented whey protein, pearl millet and milk drinks, fermented sheep’s milk, plant-based medicinal food drinks, fermented goji berry juice, soya yoghurt, fermented chickpeas, and fermented chestnut protein. The results of the study indicate that fermentation by lactic acid bacteria, yeast, and moulds is capable of enhancing nutritional content, protein digestibility, and mineral bioavailability, as well as producing bioactive components such as functional peptides, essential amino acids, phenolics, flavonoids, D-pinitol, myo-inositol, γ-aminobutyric acid (GABA), polysaccharides, and short-chain fatty acids. These components contribute to antioxidant, anti-inflammatory, anti-diabetic, and anti-cancer activities, as well as improved metabolism, bone health, and the maintenance of gut microbiota. Consequently, fermented foods have the potential to be developed as functional foods to support the prevention and management of degenerative diseases.